Investment in water, sewage and waste disposal in Norwegian local governments - Hopland, Arnt O.; Haraldsvik, Marianne; Kvamsdal, Sturla (Property management, 2023)
PurposeDescribe the trends in investments in the water, sewage and waste disposal sector (WSD) in Norwegian local governments and search for determinants that can explain variations in investment levels across local governments. The water, sewage and WSD is the second most important sector in Norwegian local governments in terms of the share of total investments and is subject to much debate due to aging pipelines in many communities. However, as pipelines are hidden in the ground, this is also a sector that can easily be forgotten until an actual failure in the system occurs.Design/methodology/approachThe authors analyze a large data set of all Norwegian local governments in the period 2003–2018 using descriptive statistics and regression techniques.FindingsThe investment levels are driven by need, in terms of expectations of a growing population, and fiscal capacity. Hence, the authors conclude that the investment decisions seem to be mostly based on reasonably rational evaluations of the local governments' future needs and capacity to pay for investments.Originality/valueThe paper contributes to the literature on determinants of public capital expenditures. An important part of this debate is whether differences in expenditure levels reflect rational decisions based on changes in need and fiscal capacity or shortsighted policy decisions.